2020
DOI: 10.1042/bsr20191248
|View full text |Cite
|
Sign up to set email alerts
|

Wnt10b promotes hair follicles growth and dermal papilla cells proliferation via Wnt/β-Catenin signaling pathway in Rex rabbits

Abstract: Wnt signaling plays an important role in the growth and development of hair follicles (HFs). Among the signaling molecules, Wnt10b was shown to promote the differentiation of primary skin epithelial cells toward the hair shaft and inner root sheath of the HF cells in mice in vitro. Whisker HFs were isolated from Rex rabbits and cultured in vitro to measure hair shaft growth. Meanwhile, dermal papilla cells (DPCs) were isolated and cultured in vitro. Treatment with AdWnt10b or the Wnt/β-Catenin Pathway inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
2
35
1
Order By: Relevance
“…Our study falls into this category. Similar to our study, Wu et al [17] found that Wnt10b promotes DPCs' proliferation in Rex rabbits. In contrast, Yu et al [59] demonstrated that mitotic arrest-deficient protein 2B (MAD2B) plays a negative role in T cell factor 4 (TCF4)-induced DPCs' proliferation in humans.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study falls into this category. Similar to our study, Wu et al [17] found that Wnt10b promotes DPCs' proliferation in Rex rabbits. In contrast, Yu et al [59] demonstrated that mitotic arrest-deficient protein 2B (MAD2B) plays a negative role in T cell factor 4 (TCF4)-induced DPCs' proliferation in humans.…”
Section: Discussionsupporting
confidence: 92%
“…In the process of HF transformation from telogen to anagen, DPCs migrate upward and then reach the bulge. In the bulge, DPCs release signals to activate multiple signaling pathways, especially the Wnt/β-catenin signaling pathway [17], stimulate the differentiation of HFSCs, and promote HF regeneration [18]. In cashmere goat, dermal papilla cells of secondary hair follicle (SHF-DPCs) are the controlling centers of SHF growth.…”
Section: Introductionmentioning
confidence: 99%
“…The latest studies carried out on in vitro hair follicle cultures isolated from Rex rabbits showed that Wnt10b promotes hair follicle growth and proliferation of dermal papilla cells (DPCs) through the activation of the Wnt/β‐Catenin signaling pathway (Wu et al . 2020).…”
Section: Molecular Control Of Hair Coat Development In Rabbitsmentioning
confidence: 99%
“…Second, the proliferation of DPCs is promoted by the overexpression or inhibition of endogenous genes. Wu et al 17 found that Wnt10b promotes DPC proliferation in Rex rabbits. In contrast, Yu et al 18 demonstrated that mitotic arrest‐deficient protein 2B plays negative roles in T‐cell factor 4–induced DPC proliferation in human beings.…”
Section: Introductionmentioning
confidence: 99%